Investigation of the Mechanical Behavior of Polystyrene using Molecular Dynamics. Issue 1 (18th November 2019) - Ries, Maximilian; Steinmann, Paul; Pfaller, Sebastian
Abstract: Polymer nanocomposites exhibit highly promising material properties caused by their molecular structure. Multiscale techniques are used to gain a deeper understanding of the influence of molecular mechanisms on the macro scale. Especially domain composition coupling approaches, e.g. the Capriccio method [1], require a precise match of the constitutive models of the coupled domains. To this end, in this contribution a methodology to characterize the material behavior of polymers using the widely used Molecular Dynamics approach is presented. Exemplary, polystyrene is investigated as a model system and the results of time proportional and time periodic uniaxial deformation tests as well as relaxation and creep tests are briefly discussed.